Portable Pico-hydro Power Plant with Archimedes Screw Turbine in Pelangi Reservoir of Universitas Islam Indonesia - iftitah imawati; Millen Febiansyah; Enaya Kafka Garuda Novtrianda; Husein Mubarok (Faculty of Engineering, Universitas Tanjungpura, 2022)
Indonesia has a lot of potential to build hydroelectric power plants because of its size and abundance of water. As in the Islamic University of Indonesia, there is a Pelangi Reservoir which has the potential to develop a pico-hydro power plant. A portable pico hydro system is needed to generate electricity properly. In this study, the pico hydro generator system was designed starting from the turbine, pulley, generator, controller, battery to the load. In the process, the voltage and current generated by this portable pico hydro generator system will be observed. By using a screw turbine, the team designed the system to optimally utilize Pelangi Reservoir water flow. The DC generator was chosen as a converter of kinetic energy into electrical energy because with low rotation, and a stable DC generator produces direct electricity. Several changes from design to reality were made so that the system could work according to field conditions and not damage the ecosystem around Pelangi reservoir. According to the test results, the current pico-hydro system at Pelangi Reservoir UII can generate a maximum power of 8.544 watts and an average discharge of 7.1532 L/second. The power can increase if the water flow has a larger discharge. If the large discharge flow is balanced by the robustness of the turbine and system. At low conditions, the system can charge a battery with a capacity of 12 volts 4 Ah with a water flow rate of 4.807 L/second, which is 9.9 volts to 12.2 volts in 36 minutes. The efficiency of hydroelectric power generation (Pico-hydro) then increases to 16.71%. The system can generate 86.49 watts of electricity at 1500 rpm on the generator.